Aplikasi Voice To Text Sekretariat DPRD Kabupaten Hulu Sungai Tengah - Abdul Ghani, Muhammad; Hamid, Abdul; Annaningtyas, Cucut (Indonesian Journal of Information Technology and Computing (IMAGING), 2023)
Meetings are routine events in the function of legislation. The main purpose of the meeting is to record the minutes of the meeting accurately and completely, which is time consuming and carries the risk of typos. Therefore, this study aims to implement a voice to text application at the DPRD Secretariat of Hulu Sungai Tengah Regency in order to improve the efficiency of recording the minutes of meetings. This application uses speech recognition technology to automatically convert the speech of meeting participants into text. This research examines several meetings and measures the time required to enter meeting notes manually and use a voice to text application. The results show that using this application can save up to 50% time and reduce the risk of typos. Apart from that, this application allows users to edit and correct text easily. Therefore, this study recommends the implementation of the voice to text application at the DPRD Secretariat of Hulu Sungai Tengah Regency as an effective alternative to increase the efficiency of recording the minutes of meetings.